Karakteristik Biji Kakao Hasil Fermentasi Kapasitas Kecil dengan Jenis Wadah dan Lama Fermentasi yang Berbeda - Ni Luh Putu Novi Adi Aryani; Ni Luh Yulianti; Gede Arda (Jurnal BETA (Biosistem dan Teknik Pertanian), 2018)
This study aimed to determine the characteristics of fermented cocoa beans in small-capacity containers and to identify the treatment that produces the best cocoa bean characteristics after fermentation. A factorial randomized block design with two factors was used. The first factor was container type with three levels: wooden box, bamboo basket, and plastic sack. The second factor was fermentation length with three levels: 4 days, 5 days, and 6 days. Observed parameters included fermentation temperature, external and internal cocoa bean pH, number of beans per 100 grams, skin content, water content, and split test results (unfermented, underfermented, fermented, germinating, moldy, and insect-containing beans). The results showed that both container type and fermentation time significantly affected fermentation temperature, pH, number of beans per 100 grams, skin content, water content, and split test results for unfermented and fermented beans. The best cocoa bean characteristics were obtained using a wooden box (25.5 cm × 25.5 cm × 30.5 cm) with a 7.5 kg capacity fermented for 6 days, achieving a maximum fermentation temperature of 45.45°C, external cocoa bean pH of 6.40, internal cocoa bean pH of 4.10, 87.5 beans per 100 grams, skin content of 10.95%, water content of 7.3%, and split test results of 0% unfermented, 8% underfermented, 92% fermented, 0% germinating, 0% moldy, and 0% insect-contaminated beans.